A role for the orphan nuclear receptor TLX in the interaction between neural precursor cells and microglia. Issue 1 (22nd February 2019) - Kozareva, Danka A.; Moloney, Gerard M.; Hoban, Alan E.; Rossini, Valerio; Nally, Ken; Cryan, John F.; Nolan, Yvonne M.
Abstract: Microglia are an essential component of the neurogenic niche in the adult hippocampus and are involved in the control of neural precursor cell (NPC) proliferation, differentiation and the survival and integration of newborn neurons in hippocampal circuitry. Microglial and neuronal cross-talk is mediated in part by the chemokine fractalkine/chemokine (C-X3-C motif) ligand 1 (CX3CL1) released from neurons, and its receptor CX3C chemokine receptor 1 (CX3CR1) which is expressed on microglia. A disruption in this pathway has been associated with impaired neurogenesis yet the specific molecular mechanisms by which this interaction occurs remain unclear. The orphan nuclear receptor TLX (Nr2e1; homologue of the Drosophila tailless gene) is a key regulator of hippocampal neurogenesis, and we have shown that in its absence microglia exhibit a pro-inflammatory activation phenotype. However, it is unclear whether a disturbance in CX3CL1/CX3CR1 communication mediates an impairment in TLX-related pathways which may have subsequent effects on neurogenesis. To this end, we assessed miRNA expression of up- and down-stream signalling molecules of TLX in the hippocampus of mice lacking CX3CR1. Our results demonstrate that a lack of CX3CR1 is associated with altered expression of TLX and its downstream targets in the hippocampus without significantly affecting upstream regulators of TLX. Thus, TLX may be a potential participant in neural stem cell (NSC)–microglial cross-talk and may be an important target in understanding inflammatory-associated impairments in neurogenesis.